Immersive Culinary Simulation With FSM-Based NPCs in a 3D Game for Promoting Sundanese Restaurants - Sri Rahayu; Egha Satria Bagaskara; Dewi Tresnawati; Yosep Bustomi (Universitas Multimedia Nusantara, 2026)
The development of a 3D interactive game entitled “Sapiring Rasa” aims to promote traditional Sundanese restaurants while supporting the preservation of Indonesia’s culinary heritage through digital media. The game is designed for desktop platforms with a top-down perspective, allowing players to manage a traditional eatery, serve customers, and address various resource management challenges. The development process employed the Unity3D Engine and applied the Multimedia Development Life Cycle (MDLC), which includes the stages of Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The main contribution of this study lies in the practical implementation of artificial intelligence–based non-player characters (NPCs) using a Finite State Machine (FSM) approach to create dynamic and responsive customer interactions, thereby improving gameplay immersion and user experience. System functionality was validated through alpha testing using black-box methods, while usability evaluation was conducted through beta testing using the System Usability Scale (SUS) involving 30 participants. The results showed an average SUS score of 73.5, classified as “Good” and “Acceptable.” These findings indicate that the proposed game is usable and well received by users. Overall, the integration of local cultural elements into interactive gameplay demonstrates the potential of digital games as effective media for cultural promotion and educational purposes.